2022
DOI: 10.48550/arxiv.2201.08911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The forward and reverse shock dynamics of Cassiopeia A

Jacco Vink,
Daniel J. Patnaude,
Daniel Castro

Abstract: We report on proper motion measurements of the forward-and reverse-shock regions of the supernova remnant Cassiopeia A (Cas A), including deceleration/acceleration measurements of the forward shock. The measurements combine 19 years of observations with the Chandra X-ray Observatory, using the 4.2-6 keV continuum band, preferentially targeting X-ray synchrotron radiation. The average expansion rate is 0.218 ± 0.029%yr −1 for the forward shock, corresponding to a velocity of ≈ 5800 km s −1 . The time derivative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 65 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…The discrepancies between models and observations might originate from the idealized and simplified description of the asymmetric shell adopted in our models. For instance, observations have shown some density enhancements in the north-east region (Weil et al 2020), where some evidence for deceleration of the forward shock was recently reported (Vink et al 2022). These findings suggest that the CSM structure may be more complex than modeled here.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…The discrepancies between models and observations might originate from the idealized and simplified description of the asymmetric shell adopted in our models. For instance, observations have shown some density enhancements in the north-east region (Weil et al 2020), where some evidence for deceleration of the forward shock was recently reported (Vink et al 2022). These findings suggest that the CSM structure may be more complex than modeled here.…”
Section: Discussionmentioning
confidence: 49%
“…Features similar to those observed by Sato et al (2018) might be obtained by rotating the asymmetric shell approximately 90 o clockwise about the y axis. In this case, however, we found that the models do not reproduce other asymmetries that characterize the reverse shock of Cas A, in particular the velocity profiles derived by Vink et al (2022) and the orientation of the offset between the geometric center of the reverse shock and that of forward shock (Gotthelf et al 2001). In Appendix A, we present an example of these models.…”
Section: Reverse Shock Asymmetries At the Age Of Cas Amentioning
confidence: 93%
See 3 more Smart Citations